Characterization of Bioplastic Compostable PLA-Cellulose Based as Eco-friendly Packaging - Karim, Wouda Fiorendita; Harahap, Muslim Arfanshah; Prakoso, Mochamad Galih; Finaldin, Muhammad Alhas; Kemala, Tetty (Indonesian Journal of Chemical Science, 2021)
Bioplastics have the potential a substitute for conventional plastics. Bioplastics can be made from PLA and cellulose formulated with organic fertilizer granules which have the potential to be environmentally friendly bioplastics because they are easily degraded in the environment. This study aims to determine the effect of adding granulated organic fertilizer (POG) to compostable bioplastics and to analyze its potential as environmentally friendly packaging. Bioplastics are made from PLA granules and cellulose with the same ratio of 95%: 5% and POG with a variation of 0.00 g; 0.50 g; 1.00 g; 1.50 g; and 2.00 g in 5.00 g (PLA-cellulose). The resulting bioplastics were investigated for their properties, including water vapor transmission rate, density, water absorption, and mechanical properties. The results showed that the addition of granule organic fertilizer (POG) had an effect on the rate of water vapor transmission, density, and mechanical properties of bioplastics and also provided good quality as environmentally friendly packaging. The elongation of bioplastic with the addition of 2 g of POG has a value of 11.86% water vapor transmission rate while the density of the addition of POG shows no significant difference.